2014
DOI: 10.3389/fonc.2014.00020
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Effects on Socio-Economic Inequalities of Introducing HPV Testing as Primary Test in Cervical Cancer Screening Programs

Abstract: Background: Screening with HPV is more effective than Pap test in preventing cervical cancer. HPV as primary test will imply longer intervals and a triage test for HPV positive women. It will also permit the development of self-sampling devices. These innovations may affect population coverage, participation, and compliance to protocols, and likely in a different way for less educated, poorer, and disadvantaged women.Aim: To describe the impact on inequalities, actual or presumed, of the introduction of HPV-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 114 publications
1
24
1
Order By: Relevance
“…The participants represented a mix of socioeconomic circumstances and the focus groups integrated both regularly screened and under-screened women. Beyond the equity issues that are often addressed in relation to studies on self-HPV acceptability, 1 , 4 our results suggest that previous experience with a gynecologist plays an important role. In addition, women who had not tested self-HPV, but who were in favor of it, indicated over the course of the discussion that for safety reasons, they preferred a gynecological examination to self-HPV, as observed in previous studies.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The participants represented a mix of socioeconomic circumstances and the focus groups integrated both regularly screened and under-screened women. Beyond the equity issues that are often addressed in relation to studies on self-HPV acceptability, 1 , 4 our results suggest that previous experience with a gynecologist plays an important role. In addition, women who had not tested self-HPV, but who were in favor of it, indicated over the course of the discussion that for safety reasons, they preferred a gynecological examination to self-HPV, as observed in previous studies.…”
Section: Discussionmentioning
confidence: 59%
“… 1 Self-HPV was expected to improve the overall screening rate and reduce inequity in access to screening. The medical literature presents self-HPV as an innovative, promising, and effective alternative to the traditional Pap smear test, 2 4 offering a less intrusive procedure and increasing screening rates in previously under-screened women. 3 6 According to the results of recent randomized controlled trials, invitations for self-HPV are more often accepted than Pap smear invitations, 4 , 5 indicating that screening participation is increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore worrying that even in the presence of gynaecological services at the HIV clinic these women who are not yet on cART are less likely to receive consultations. A special focus should be put on patients entering care to make sure they understand the importance of gynaecological screening and of following the physician's recommendations [17].…”
Section: Discussionmentioning
confidence: 99%
“…Giorgi Rossi and colleagues present an algorithm to model the impact on inequalities of introducing HPV-based screening of cervical cancer ( 1 ). They found that knowledge about HPV and cervical cancer was lower in women with low socio-economic status and in disadvantaged groups.…”
mentioning
confidence: 99%